Palladium-catalyzed C8–H arylation and annulation of 1-naphthalene carboxylic acid derivatives with aryl iodides. Issue 13 (22nd April 2021) - Zhang, Min; Fu, Zhangyi; Luo, Anping; Pu, Xingwen; Wang, Menglei; Huang, Ying; Yang, Yudong; You, Jingsong
Abstract : Disclosed herein is palladium-catalyzed C8–H arylation and annulation of 1-naphthoic acid derivatives with aryl iodides in a low reactant molar ratio via an electrophilic aromatic substitution (SE Ar) process. Abstract : The discovery of a concise route enabling site-selective arylation of polycyclic aromatic hydrocarbons (PAHs) with easily available aryl sources is an appealing yet challenging task toward the bottom-up preparation of π-extended PAHs. Disclosed herein is a palladium-catalyzed C8–H arylation of 1-naphthoic acid derivatives with aryl iodides in a low reactant molar ratio via an electrophilic aromatic substitution (SE Ar) process. In addition, a C8–H annulation protocol is developed to rapidly assemble benzanthrones by simply switching the solvent to 1, 1, 1, 3, 3, 3-hexafluoropropan-2-ol (HFIP).